Cicling as a vector of a territorial development - Fermín Rodríguez Gutiérrez (Boletín de la Asociación de Geógrafos Españoles)
The potential of cycling as a sport is addressed specifically from the territorial point of view, totally determined by geography, which should make it as an object of attention from this discipline, in order to assess its role in certain countries and the ability of these to use it as a vector of territorial development. A smart strategy is developed to define its expansion in a region and a methodology is showed to create a territorial machine tool called «Cyclist Ring» embodying the contribution of cycling to a development strategy and to give substance to a territorial brand, linking a particular territory, landscape, sport, industrious activity, tourism expertise, experience and controlled effort.